Sustainable road transport practices and challenges in Ethiopia: Sidama National Regional State - Siquarie Shudda Dangisso; R. Dayanandan; Wogene Markos (Journal of Sustainable Development of Transport and Logistics)
Purpose: To investigate sustainable road transport practices and the challenges facing Sidama Region, Ethiopia, in the context of national development goals. Methodology: The study uses a qualitative approach, including focus group discussions, key informant interviews, and document analysis, analyzed thematically with NVivo software and grounded in theories of accessibility, mobility, and sustainability.      Results: The research identifies significant challenges: policy fragmentation, underdeveloped infrastructure, limited adoption of intelligent transport solutions, weak stakeholder engagement, and environmental sustainability gaps. Theoretical Contribution: The study applies and tests established transport theories in a new regional context, highlighting the gap between policy aspirations and practical outcomes. Practical Implications: Recommendations include improved policy alignment, investment in infrastructure and human capital, stronger public-private partnerships, and adoption of green technologies to advance sustainable transport in Sidama.